(untitled) (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To determine the clinical outcome of rheumatic heart disease in pregnancy. Methods: Retrospective cross-sectional descriptive study from April 2019 to April 2021 in Nobel Medical College, Biratnagar, Nepal. Feto-maternal variables were taken for their health status. Data presented in table with frequency. Results: Out of 13013 deliveries in a year, 49 had cardiac disease (0.37%) and 38 had rheumatic heart disease (0.29%) over 28 weeks of gestation; 95% (n=36) had mitral valve involvement; 12 were primigravida and 7 preterm at the time of delivery. Half of them underwent caesarean section for various indications. Most common maternal complications were cardiac failure, cardiac arrythmia, admission to ICU, obstetric complications, including maternal mortality in 5.2% (n=2) cases. Low birth was in 29% (n=11) of cases, and 34% (n=13) of them needed NICU care at the time of delivery. There was history of rheumatic fever in 9 cases (24%). Conclusions: Rheumatic heart disease is the commonest diagnosis among heart disease in pregnancy and adverse event can be minimized by multidisciplinary intervention